2021
DOI: 10.3390/s21186014
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Roadway Pavement Marking Maintenance Using Lane Keep Assist Sensor Data

Abstract: There are over four million miles of roads in the United States, and the prioritization of locations to perform maintenance activities typically relies on human inspection or semi-automated dedicated vehicles. Pavement markings are used to delineate the boundaries of the lane the vehicle is driving within. These markings are also used by original equipment manufacturers (OEM) for implementing advanced safety features such as lane keep assist (LKA) and eventually autonomous operation. However, pavement markings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The objective of this study is to determine if lane width measurements from sensors onboard production vehicles can be used to screen public road networks for sections that have less than prescribed lane widths. Previous studies have found many uses for connected vehicle data, including pavement marking evaluation, traffic signal performance, and crash mitigation through surrogate safety measures and hard braking [ 17 , 18 , 19 , 20 , 21 ]. The benefit of using production vehicle data is that it can be crowdsourced and provide ubiquitous coverage across the state without resource-intensive deployments and data collection.…”
Section: Objectivementioning
confidence: 99%
“…The objective of this study is to determine if lane width measurements from sensors onboard production vehicles can be used to screen public road networks for sections that have less than prescribed lane widths. Previous studies have found many uses for connected vehicle data, including pavement marking evaluation, traffic signal performance, and crash mitigation through surrogate safety measures and hard braking [ 17 , 18 , 19 , 20 , 21 ]. The benefit of using production vehicle data is that it can be crowdsourced and provide ubiquitous coverage across the state without resource-intensive deployments and data collection.…”
Section: Objectivementioning
confidence: 99%
“…Although exact cause of this excess salt is not clear, this often occurs when the hydraulic driven salt spreader on the truck is not properly calibrated. In addition to being costly, creating unnecessary environmental impact, it also can make viewing the lane lines difficult for both human drivers and advanced driver assistance systems (ADAS) that rely on detecting lane markings [13]. The Ohio Department of Transportation found the accuracy for bed scale sensors embedded on its snowplows varied from 2.2% to 8.4% for calibrated and uncalibrated sensors respectively [14].…”
Section: Motivationmentioning
confidence: 99%
“…In August 2020, more than 167 billion passenger car trajectory waypoints were collected across 11 states [3]. Granular information received from individual vehicles have been curated for a variety of applications such as work zone monitoring [4] [5] [6], assessment of winter operations [7] [8], performance at intersections [9] [10] [11] and assessment of roadways in general [3] [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%